Aspects of intensive therapy of diabetic ketoacidosis in pediatric practice (literature review) - Yu. V. Bykov; А. А. Muravyeva (Вестник анестезиологии и реаниматологии)
Diabetic ketoacidosis (DKA) is an acute and severe complication of type 1 diabetes mellitus that is associated with a high risk of cerebral edema (CE)and may result in death. DKA is characterized by acute hyperglycemia, ketonemia and metabolic acidosis in the setting of decreased levels of insulin and excessive levels of the counter regulatory hormones. Algorithms of intensive treatment of DKA include such steps as fluid replacement therapy, correction of electrolyte imbalances, and intravenous infusion of insulin, performed in order to resolve metabolic acidosis and hyperglycemia as well as to prevent the development of complications (CE and hypokalemia). The analysis of literature has shown that during fluid replacement the most preferred options are balanced crystalloid solutions (Hartman’s solution and Plasma-Lyte). Infusion therapy is divided into bolus (administration of crystalloid solutions at the rate of 10 ml / kg for 30-60 minutes) and maintenance (administration of solutions for 24-48 hours). Intravenous glucosesolutions (5–10 %) are infused when the patient’s blood glucose falls below 14–16 mmol/L. Electrolyte disturbances (hypokalemia and hyponatremia) are resolved by prompt intravenous infusion of potassium and sodium solutions. Intravenous infusion of insulin is started at the rate of 0.05–0.1 U/kg/h, not earlier than 1 hour after the initiation of fluid resuscitation. Successful treatment of DKA in pediatric practice relies on clear understanding of the pathophysiological mechanisms of this complication and knowledge of the doses of the pharmaceutical drugs and volumes of infusion solutions to be used.